2019
DOI: 10.1016/j.mechmachtheory.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate analysis of the four-bar linkage

Abstract: Uncertainties are inherent in the fabrication and operation of mechanisms. In terms of the four-bar linkage, uncertainties in the geometric parameters result in non-exact solutions for the coupler point. A design description which accounts for bounded uncertainties is termed an appropriate design. Appropriate analysis routines are analysis routines for guaranteeing that specific requirements will be satisfied, which is applicable to mechanisms described by an appropriate design. These routines rely on interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…For these phases, [k] denotes the known variables and [u] denotes the unknown variables , bisection allows the entire unknown search space to be reliably explored and therefore a general solving routine is guaranteed to be able to find all solutions to the considered problem. A detailed overview of the three phases is provided in [23].…”
Section: Overview Of Interval Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…For these phases, [k] denotes the known variables and [u] denotes the unknown variables , bisection allows the entire unknown search space to be reliably explored and therefore a general solving routine is guaranteed to be able to find all solutions to the considered problem. A detailed overview of the three phases is provided in [23].…”
Section: Overview Of Interval Analysismentioning
confidence: 99%
“…The equations describing the kinematics of the four-bar linkage, formulated using a coordinate representation, are given in Eq. (5) (see [23] for the formulation). This formulation is preferable for use with interval analysis methods due to the minimal occurrence of variables in the equations, which reduces the effects of the interval dependency problem.…”
Section: Four-bar Linkage Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was reported that the differential pressure caused by the butterfly valves could be used for flow measurement [12,13]. Different from other kinds of butterfly valves, the link rod butterfly valve uses a four-bar linkage mechanism to drive the valve plate [14][15][16]. Since the moving path of the valve plate could be accurately designed via optimization of the linkage mechanism, the friction between the sealing pair on the valve seat and valve plate is drastically reduced and reliable sealing could be achieved.…”
Section: Introductionmentioning
confidence: 99%